TIME TO USE MRI FOR RISK STRATIFICATION IN SYMPTOMATIC CAROTID STENOSIS?. Issue 12 (15th November 2016) - Hosseini, Akram; Simpson, Richard; Altaf, Nishath; Bath, Philip; MacSweeney, Shane; Auer, Dorothee
Abstract : Introduction: MRI-defined carotid plaque haemorrhage (MRIPH) can predict recurrent cerebrovascular ischaemic events in severe symptomatic carotid stenosis. It is less clear whether MRIPH can improve risk stratification in less severe disease. Methods: 192 symptomatic participants with 30–99% carotid artery stenosis who were clinically deemed not to benefit from carotid endarterectomy were recruited to undergo MRI and clinical follow-up (mean 22 months; range: 3–1587 days). The clinical Carotid Artery Risk (CAR) score could be evaluated in 88 patients. MRIPH was defined as plaque intensity >150% that of adjacent muscle. Survival analyses were performed with recurrent stroke or diffusion-positive-cerebral ischaemia as the main endpoint. Results: 151 fulfilled the inclusion criteria (age: 77, 60.5% men); 55 were MRIPH+ve. 47 had low, 36 intermediate and 5 high CAR scores. Cox regression showed MRIPH as a strong predictor of future infarction (HR=5.0, 95% CI=1.6–15.9, P=0.006, corrected for degree of stenosis), also in the subgroup with 50–69% stenosis (HR=4.1, 95% CI=1–16.8, P=0.049). The absolute risk of future infarction was 31.7% at 3 years in MRIPH+ve versus 1.8% in MRIPH-ve (P<0.002). MRIPH increased cumulative risk difference of future infarction by 47.1% at 3 years in those with intermediate CAR score (P=0.004). Conclusion: MRIPH can identify a subgroup of patients with a higher risk than clinically predicted thus enabling targeted intervention.